Increasing self-efficacy to improve the transition to university: an Australian case study - Schütze, Heike; Bartyn, Jenna; Tapsell, Amy (Journal of further and higher education, 2021)
The first-year university experience is inherently linked to student satisfaction, retention and academic success. A sense of academic preparedness can enhance the first-year transition experience. Subjects designed to assist students to transition to university can improve the transition experience; however, there is very limited evidence of their successful implementation in Australia. An interdisciplinary credit-bearing subject underpinned by the Learning by Doing Approach and the Theory of Self-efficacy, was developed and implemented in an Australian university. Students' baseline (pre-test) and follow-up (post-test) survey responses on their self-perceived levels of knowledge and confidence in academic skills were compared to test for significant differences. Students reported greater knowledge and confidence with regards to the academic skills required for university. The subject's highly scaffolded nature ensured students actively engaged in individual and collaborative activities that allowed them to learn as they constructed knowledge. As students learnt new skills in a supportive learning environment, they incorporated these skills into their learning and utilised them in their other subjects, which increased their confidence and self-efficacy. Similar interdisciplinary credit-bearing transition subjects may be beneficial in other universities to help support students transitioning to university. Longitudinal research is required to determine the effectiveness on academic outcomes and retention.